1987
DOI: 10.1254/jjp.45.493
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological properties of SM-3997: A new anxioselective anxiolytic candidate.

Abstract: Abstract-Pharmacologicalproperties of SM-3997 (3aa,4Q,7(9,7aa-hexahydro-2 (4-(4-(2-pyrimidinyl)-1-piperazinyl)-butyl)-4,7-methano-1 H-isoindole-1,3(2H) dione dihydrogen citrate) have been examined in rats and mice. SM-3997 showed a dose-related anticonflict activity in rats in a water lick conflict paradigm, and it had no effect on water consumption in a spontaneous water drinking test. The potency of SM-3997 appeared to be equal to that of buspirone and about one-half that of diazepam.No tolerance to the anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
1

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 84 publications
(30 citation statements)
references
References 14 publications
0
29
1
Order By: Relevance
“…All other azapirones that are clinically effective also bind selectively to 5 HT1A receptors (22). Moreover, we have also demonstrated that tandospirone acts on 5 HT1A receptors as an agonist in behavioral, biochemical and electrophysiological studies (10,19,(23)(24)(25)(26). In the light of these facts, the possibility exists that the agonist action of tandospirone on 5-HT1A receptors, but not benzodiazepine receptors, is related to its con flict effect.…”
Section: Discussionmentioning
confidence: 69%
See 3 more Smart Citations
“…All other azapirones that are clinically effective also bind selectively to 5 HT1A receptors (22). Moreover, we have also demonstrated that tandospirone acts on 5 HT1A receptors as an agonist in behavioral, biochemical and electrophysiological studies (10,19,(23)(24)(25)(26). In the light of these facts, the possibility exists that the agonist action of tandospirone on 5-HT1A receptors, but not benzodiazepine receptors, is related to its con flict effect.…”
Section: Discussionmentioning
confidence: 69%
“…For example, in rat conflict tests, which are the most widely used animal behavioral para digms for recognizing potential anxiolytic drug activity, some groups, including our own, were able to demonstrate anticonflict activities of azapirones (5,(12)(13)(14), while others failed to find any positive effects (15)(16)(17). Moreover, in the former cases, the efficacies of azapir ones were substantially lower than those of benzodiazepines.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We previously reported that SM-3997 did not directly interact with GABA receptor/CI channel complexes, but is suggested to have 5-HT1A agonistic properties by pharmacolo gical, biochemical and electrophysiological experiments (1)(2)(3)(4)(5). The present study was conducted to determine the regional distribu tion of 5-HT,,, receptors and SM-3997 binding to these receptors in the rat brain.…”
Section: Benzodiazepinesmentioning
confidence: 83%